STRATEGI GURU DALAM MENINGKATKAN LITERASI SISWA SEKOLAH DASAR DI ERA DIGITAL: TINJAUAN LITERATUR SISTEMATIS - Abd. Rahman Hamdan; Aisyah; Soviatul Laili; Yunita Dian Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digitalization presents new challenges in strengthening literacy among elementary school students, particularly in their ability to comprehend, evaluate, and interpret information. This study aims to examine the implementation of various strategies to enhance elementary school students’ literacy in the digital era through a literature review approach. The research method employed a thematic and descriptive-analytical review of relevant journal articles, proceedings, and scholarly sources. The findings indicate that literacy improvement is shaped by the interaction of instructional strategies, school support, family involvement, and patterns of digital technology use. Effective literacy strategies operate through a combination of habit formation, modeling, interaction, and motivational reinforcement, including reading habituation, read-aloud activities, retelling stories, literacy games, and adequate access to reading materials. The novelty of this study lies in its integrative synthesis of literacy strategies into a systemic conceptual framework that positions literacy as a multidimensional and sustainable educational practice. These findings provide both conceptual and practical references for teachers and schools in designing adaptive literacy strategies in the digital era.